Exploring HIV-Related Stigma and Discrimination at the Workplace in Southwestern Uganda: Challenges and Solutions - Benedict Twinomugisha; Fungisai Gwanzura Ottemöller; Marguerite Daniel (Advances in Public Health)
Globally, the HIV/AIDS pandemic continues to have an enormous impact on affected societies. Despite several health promotion interventions being carried out, HIV/AIDS remains a major cause of deaths in low and middle income countries. At the workplace, the pandemic has brought about reduction in productivity, increased staff turnover, increased production costs, high levels of stigma, etc. HIV stigma is one of the main reasons why the pandemic has continued to devastate a number of societies around the world. HIV stigma presents barriers to HIV prevention in different settings including the workplace. Unlike large enterprises, small-scale enterprises have received less attention in the fight against HIV/AIDS. This study’s purpose was to explore how employers and employees can overcome challenges of HIV-related stigma at the workplace. This study employed a qualitative case study design. Data were collected from eighteen participants in three small-scale enterprises in Kabale. Findings indicate that small-scale enterprises are faced with the fear of HIV testing, status disclosure, staff turnover, suicidal thoughts, gossip, etc. Implementing operative national HIV workplace policies may enable small-scale enterprises to overcome challenges of HIV-related stigma at the workplace.